Implementasi Pembelajaran Ipas Materi Bentang Alam Berbasis Kurikulum Merdeka Belajar pada Siswa Kelas IV SDN 1 Damar (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
This study aims to describe the implementation of IPAS learning on landscape materials based on the Merdeka Curriculum for fourth-grade students at SDN 1 Damar. The learning process was conducted using the Problem Based Learning (PBL) model, which emphasizes solving contextual problems related to students’ daily lives. This research employed a qualitative descriptive method, with the subjects consisting of fourth-grade students and classroom teachers. Data were collected through observation, interviews, and documentation. The results indicate that the implementation of IPAS learning on landscape materials using the PBL model enhances students’ active participation, critical thinking skills, collaborative abilities, and environmental awareness. Students were actively involved in identifying landscape-related problems, engaging in discussions, and presenting simple solutions. Nevertheless, several challenges were identified, including students’ readiness and limited support from the family environment. Overall, IPAS learning based on the Merdeka Curriculum using the PBL model can be effectively implemented and contributes to strengthening the Pancasila Student Profile